PENGARUH PENYULUHAN TENTANG PENTINGNYA POSYANDU TERHADAP PERSEPSI IBU DI POSYANDU DUSUN NGRAYUNG DESA KEPUHPANDAK KECAMATAN KUTOREJO KABUPATEN MOJOKERTO - Dewi Yanti, Ariu; Mayasari, Devi (JURNAL KEPERAWATAN SEHAT, 2016)
Public perception that bad of the Posyandu causes lack of knowledge of mothers about the importance posyandu. This study aims to analyze influence of counseling about importance posyandu of the mothers perception about posyandu in Hamlet Village Ngrayung Kepuhpandak Kutorejo District of Mojokerto. This study uses the analytical method of pre experimental one-group pretest-posttest design. With population of all mothers with children under five in Hamlet Village Ngrayung Kepuhpandak Kutorejo District of Mojokerto amounted to 77 people. Sampling technique used was purposive sampling with a sample of 50 respondents who fit the desired criteria of researchers. The collection of data using a questionnaire designed researchers themselves then the data were analyzed by using Wilcoxon test. From the research results are changing the perceptions before and after conseling is before conseling where 24 respondents were negative perception and after counseling become 34 respondents perception positive. Wilcoxon test results showed ρ = 0.012, ρ < α (0.05), meaning H? rejected so that influence conseling about the importance posyandu the perception of mothers about posyandu in Hamlet Village Ngrayung Kepuhpandak Mojokerto. This suggests that education can increase knowledge and understanding of a person. Therefore, conseling is very important for the community that the advice for health care workers and others institute to more frequent providing conseling.Keywords:Conseling, Posyandu, Mother’s Perception